Dihydroisoindolo[2,1-a]quinazoline-5,11-dione derivatives as potent and selective inhibitors targeting hepatitis B virus - Zhang, Jun-Fei; Liu, Bo; Chen, Cong-Xin (Bangladesh Journal of Pharmacology, 2015)
The construction of dihydroisoindolo[2,1-a]quinazoline-5,11-dione derivatives (4a4m), by the condensation isatoic anhydride, appropriate amines and 2-formylbenzoic acid by using silica sulfuric acid as catalyst was reported. These dihydroisoindolo[2,1-a]quinazoline-5,11-dione derivatives (DIQ) were identified as potent inhibitors of HBV capsid assembly. The newly synthesized dihydroisoindolo[2,1-a]quinazoline-5,11-dione derivatives 4a-4m were characterized by 1H NMR, 13C NMR, and Mass spectrum and evaluated for their anti-HBV activity. Majority of the synthesized compounds inhibited the expression of viral antigens at low concentration. But five compounds, 4a, 4b, 4c, 4f, and 4m were shown potent inhibition of HBV DNA replication at submicromolar range. Of these compounds, compound 4a was the most active when compared with lamivudine.